Pengaruh Kepemimpinan dan Motivasi Terhadap Kepuasan Kerja Pegawai pada PD.BPR BKK Blora - Candra Ayu Dwi Shintiya; Muliawan Hamdani (ECONBANK: Journal of Economics and Banking, 2020)
This study aims to determine the effect of leadership and motivation on employee job satisfaction at PD BPR BKK Blora. The sampling technique used in this study is a census, where the entire population is taken as a sample of 50 employees. The analysis technique used is multiple linear regression. Based on this research, it can be seen that leadership and motivation have a positive and significant effect on job satisfaction. This result means that the better the leadership is applied, the higher the employee's job satisfaction. The existence of a leader who can generate ideas for employees at work, prioritizes partnerships with employees and empowers and involves employees in development can make employees higher job satisfaction. Likewise, motivation means that the higher the work motivation, the higher the employee's job satisfaction